A successfully treated case of dysphonia associated with bilateral interarytenoid paralysis - Shyamala Dharmaraj (Journal of All India Institute of Speech and Hearing, 1970)
The following case is reported for two reasons : (1) It is offered as an illustration of how a client with serious organic voice impairment was able to achieve extra- ordinary vocal rehabilitation through the development and improvement of overall voice and speech skills; (2) Typhoid which seems to be the etiological factor, in this case, has not been reported in any of the standard text-books to cause a voice problem. (Greene 1966; Luchsinger and Arnold 1967; Van Riper and Irwin 1958; Murphy 1964; West and Ansberry 1968; Berry and Eisenson 1962).